The Effect Of Lego Letters Media On Early Reading Ability In Children Ages 5-6 Years In Kindergarten Yasril Ananta Baharuddin Parepare City - trisnawaty, susi (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
Background : Early reading is defined as a process from written symbols (letters) into speech. Children who are often introduced to reading will get used to seeing books as a source of information. Lego as a constructive game in the form of building, organizing and managing various media around it has been commonly played by Early Childhood Children during their development. Objectives : How to describe the development of learning in children before and after using Lego media, how to describe early reading skills in children before and after using Lego media, and the effect of using Lego media on early reading skills. Method : The approach used in this study is a quantitative research approach, namely the research was conducted to analyze the effect of the experimental method on children's early reading abilities. The type of research used in this research is